2012
DOI: 10.2337/dc11-1642
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation and Prognosis in Patients With Type 2 Diabetes and Myocardial Infarction

Abstract: OBJECTIVEThe activation of the complement system may be involved in the pathology of myocardial infarction (MI) and type 2 diabetes. To explore their potential as prognostic markers, we characterized two factors in the complement cascade, the end product sC5b-9 and the mannose-binding lectin–associated Ser protease-2 (MASP-2), in type 2 diabetic patients with suspected MI.RESEARCH DESIGN AND METHODSPlasma sC5b-9 and MASP-2 were determined in patients with MI and type 2 diabetes (n = 397; median age 70; male 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 22 publications
(36 reference statements)
3
35
2
2
Order By: Relevance
“…The protective effects of CD59 were confirmed by another group (1017), although more equivocal results were reported by others (60,2052). These animal studies are consistent with an epidemiological study finding mildly increased risk of cardiovascular events in those having higher plasma levels of soluble C5b-9 as evidence of an activated complement system (1189). Factors earlier in the pathway were less strongly or nonsignificantly associated with risk (479).…”
Section: The Complement Pathway and Atherogenesissupporting
confidence: 65%
“…The protective effects of CD59 were confirmed by another group (1017), although more equivocal results were reported by others (60,2052). These animal studies are consistent with an epidemiological study finding mildly increased risk of cardiovascular events in those having higher plasma levels of soluble C5b-9 as evidence of an activated complement system (1189). Factors earlier in the pathway were less strongly or nonsignificantly associated with risk (479).…”
Section: The Complement Pathway and Atherogenesissupporting
confidence: 65%
“…It has later been confirmed that plasma sC5b-9 at hospital admittance is a negative prognostic factor in acute myocardial infarction (Lindberg et al, 2012;Mellbin et al, 2012).…”
Section: Evidence For Complement Activation In Coronary Heart Diseasementioning
confidence: 98%
“…MASP-2 levels were lower in both MI and stroke patients compared with healthy controls, while MASP-3 and MAp44 did not differ between groups (Frauenknecht et al, 2013). In a cohort study of individuals with T2DM, MASP-2 levels were significantly decreased in patients with acute cardiovascular events (Mellbin et al, 2012). MASP-2 levels were also lower in another study in patients with acute MI (Zhang et al, 2013).…”
Section: Masps In Cardiovascular Diseasesmentioning
confidence: 85%